Facile Sol−gel Synthesis of CoPt Nanopowder in Air Ambient: A Study for Soft Magnetic Device Applications (Bangladesh Journal of Physics, 2024)
Currently, the utilization of cobalt-based soft magnetic nanocrystalline powders spans various technological domains, encompassing magnetic heads and shields, magnetic sensors, biomedical advancements, ferro-fluid technology, among other notable applications. Herein, we elucidate the impact of the presence of oxygen on CoPt magnetic nanoparticles prepared through an easy and economical sol-gel route, and annealed at 800 °C for 3 hours in an air ambient, for the first time. The structural, elemental, morphological, vibrational and magnetic properties were investigated by XRD, TEM, FTIR spectroscopy and VSM techniques. The XRD analysis yields the tetragonal unit cell dimensions of a= 3.843 Å and c= 3.754 Å. Lattice parameters are also calculated from SAED patterns which are well agreed with the value obtained from XRD peaks. The average crystalline size calculated from W-H plot was 34 nm. EDS spectra confirmed the presence of Co, Pt and oxygen without any magnetic impurities. The average size of nanoparticles, measured from TEM images of the as-prepared nanopowder, was 67 nm, which decreased to 40 nm after annealing in air atmosphere at 800 °C for 3 hours. The magnetic coercivity value of annealed nanoparticles was 204 Oe, which is considerably smaller compared to values reported in other published research. This difference can be attributed to the presence of oxygen, revealing the soft ferromagnetic nature of the nanoparticles.Bangladesh Journal of Physics, Vol. 31, Issue 1, pp. 43 – 51, June 2024